Política criminal y seguridad ciudadana en el Ecuador - Aguaguiña, María G. (2020)
Criminal Policy is considered a legal and social strategy that is based on the ideological choices and aims to respond pragmatically to the problems related to the prevention and repression of the criminal phenomenon, understood in all your extension. For this purpose, Criminal Policy brings together all criminal sciences, penitentiary, police and finally, to the punitive jurisdictional apparatus of the State, as well as with all control social intervention policies (Azaola and Torres, 2009). A) Yes, Numerous countries have opted for a Criminal Policy that makes the custodial sentence freedom the main instrument on which you base your rate reduction expectations of criminality. Various studies have shown that this policy has meant the mass incarceration of people, a strategy that has not produced the results promised (Berti, 2017). On the other hand, it is necessary to understand that criminality is a international phenomenon, which all states face with greater or lesser success.